2017
DOI: 10.1007/s10549-017-4587-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in omission of oncotype DX but no racial disparities in chemotherapy receipt following completed oncotype DX test results

Abstract: We identified racial disparities in omission of ODX testing but no differences in chemotherapy receipt if ODX test results were obtained, suggesting increasing access to ODX testing may improve racial equality in efficacious use of adjuvant chemotherapy for ER-positive HER2-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
5
32
1
Order By: Relevance
“…These findings supplement earlier research showing that delays in the initiation of surgical treatment beyond 60 days 24 as well as delays in the time between surgery and the initiation of chemotherapy 18,23 are associated with decrements in breast cancer survival. It has been noted that therapeutically appropriate interventions, including breast reconstruction and gene expression profile testing, can drive some treatment delays 26 ; however, because reconstruction [27][28][29] and gene expression profile testing are used at similar rates 30 or lower rates [31][32][33][34] among black women and complications of breast reconstruction are similar across race, 35,36 such clinically appropriate delays are unlikely to explain the racial disparities that we have observed. Some previous literature has suggested that racial disparities in breast cancer treatment quality and timeliness may partially Cancer November 15, 2019 be explained by the characteristics of the institutions at which minority patients seek care, 37,38 their insurance status, and/or the distribution of minority patients in geographic areas with lower access or longer distance to care.…”
Section: Discussionmentioning
confidence: 72%
“…These findings supplement earlier research showing that delays in the initiation of surgical treatment beyond 60 days 24 as well as delays in the time between surgery and the initiation of chemotherapy 18,23 are associated with decrements in breast cancer survival. It has been noted that therapeutically appropriate interventions, including breast reconstruction and gene expression profile testing, can drive some treatment delays 26 ; however, because reconstruction [27][28][29] and gene expression profile testing are used at similar rates 30 or lower rates [31][32][33][34] among black women and complications of breast reconstruction are similar across race, 35,36 such clinically appropriate delays are unlikely to explain the racial disparities that we have observed. Some previous literature has suggested that racial disparities in breast cancer treatment quality and timeliness may partially Cancer November 15, 2019 be explained by the characteristics of the institutions at which minority patients seek care, 37,38 their insurance status, and/or the distribution of minority patients in geographic areas with lower access or longer distance to care.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies, including ours, have indicated that NHB women are more likely to be recommended chemotherapy and receive it than NHW counterparts. 20,23 Some studies have shown that with Oncotype DX testing, this difference in therapy decisions is mitigated. 23 In our study, we saw that this difference in treatment decision was mitigated in the low and intermediate recurrence score groups compared to women who did not receive ODX testing.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Some studies have shown that with Oncotype DX testing, this difference in therapy decisions is mitigated. 23 In our study, we saw that this difference in treatment decision was mitigated in the low and intermediate recurrence score groups compared to women who did not receive ODX testing. Data generated from clinical trials, have indicated that over prescribing chemotherapy among women with low ODX RS can lead to worse outcomes and may be a contributing factor to the observed racial disparities in BC mortality in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations